Trust and Discipline: Adolescents' Institutional and Teacher Trust Predict Classroom Behavioral Engagement following Teacher Discipline. Issue 2 (30th March 2019) - Amemiya, Jamie; Fine, Adam; Wang, Ming‐Te
Abstract : This daily diary study examined how adolescents' institutional and teacher‐specific trust predicted classroom behavioral engagement the day after being disciplined by that teacher. Within mathematics classrooms, adolescents ( N = 190; M age = 14 years) reported institutional and teacher‐specific trust and then completed a 15‐day diary assessing teacher discipline and behavioral engagement. The results indicated that, among adolescents with low teacher trust, discipline was unrelated to next‐day behavior. Contrastingly, adolescents with high teacher but low institutional trust became less engaged following discipline, whereas those with high teacher and institutional trust became more engaged. These findings suggest that adolescents interpret discipline within the social context of trust, and adolescents' trust in the institution and teacher are important for discipline to improve behavior.